The Implementation of Dynamic Society Oriented 6c Skills Assessment Instruments in Case Method and Team Based Project Learning - Rosidin, Undang; Widyastuti, Widyastuti; Kadaritna, Nina; Handoko (LPPM Universitas Negeri Jakarta, 2024)
This research aims to describe the implementation of the dynamic society-oriented 6C assessment instrument in case method and team-based project learning. This quantitative descriptive research was conducted at the Lampung University and UIN Raden Intan Lampung (RIL), in the course which were implemented case method and/or team-based project learning-chosen by purposive sampling technique. The data analysis technique was used validity, reliability, tabulation of questionnaire results, descriptive and inferential statistics. The research results show that the 6C instruments are effective implemented in case method and team-based project learning. It was also found that in the implementation of case method and team-based project learning: i) the critical, creative, computational, and collaborative thinking skills of students at the University of Lampung were higher than the students at UIN RIL; ii) students' self-compassion at UIN RIL is higher than Lampung University; and iii) there are no students which gains high category of collaboration skills.